Kit Gene in Endometrial Carcinoma: An Immunohistochemical and Mutational Analysis. Issue 2 (1st January 2011) - Vandenput, Ingrid; Debiec-Rychter, Maria; Capoen, An; Verbist, Godelieve; Vergote, Ignace; Moerman, Philippe; Amant, Frédéric
Abstract : Objective: Because the outcome of recurrent disease of endometrial carcinoma is cumbersome, the development of target treatment strategies is critical. We evaluated KIT, a receptor tyrosine kinase, to determine a potential role for imatinib mesylate in the treatment of endometrial carcinoma. Materials and Methods: Immunohistochemical analysis for KIT expression was performed on paraffin sections from 45 patients: 30 primary and 15 recurrent tumors. Fifteen primary cases were available for mutation analysis. Results: Histopathological distribution of paraffin-embedded tissue was as follows: 30 type I and 15 type II endometrial carcinoma. Histopathological distribution of fresh-frozen tissue was as follows: 8 type I and 7 type II. Cases did not show KIT expression or mutations in mutational hotspot exons of KIT gene. Conclusions: On the basis of the absence of KIT expression or mutations, endometrial carcinoma is unlikely to respond to imatinib mesylate.